(E)-1-(4-Decyloxyphenyl)-3-(4-hydroxyphenyl) prop-2-en-1-one - Ibrahim, Abdul Razak; Fun, Hoong-Kun; Ngaini, Zainab; Siti Muhaini, Haris Fadzillah; Hasnain, Hussain (US National Library of Medicine National Institutes of Health, 2009)
In the title compound, C25H32O3, the asymmetric unit contains two crystallographically independent molecules: both enone groups adopt an s-cis configuration. In the crystal, O—H⋯O and C—H⋯O intermolecular interactions form bifurcated hydrogen bonds, which generate R 1 2(6) ring motifs. These intermolecular interactions link the molecules into one-dimensional chains along the [10An external file that holds a picture, illustration, etc. Object name is e-65-0o881-efi2.jpg] direction. The crystal structure is further stabilized by C—H⋯π interactions.